An analysis of community participation, in income generating projects at the Tembisa/Kempton Park Development Center. - Chikadzi, Victor (My University, 2009)
In South Africa, citizen participation is regarded as an integral part of all social, economic and political activity. There is always an attempt to either involve citizens/communities in different programmes or at least to pretend to have involved people. Community participation is a constitutional prerogative that the broader masses should meaningfully participate in issues affecting their lives. Thus overgrowing concern by development practitioners to utilize participatory methods has become notable in recent years and participation has become an established orthodoxy within the development discourse in South Africa. The practice of participation has become embodied in what is popularly known to be people-centered development in which it is favored that community needs take precedence over those of other stakeholders when designing and implementing development projects. This study explores community participation in income generating projects at the Tembisa / Kempton Park Development Center. Using a case study as a qualitative inquiry method, the researcher sought to establish the evidence of community participation and the extent to which participants in income generating projects were involved as the main role players. The research sample constituted of 15 participants; ten were beneficiaries of income generating projects, three were staff members at the Tembisa / Kempton Park Development Center and two participants where drawn from the main funders of the Tembisa / Kempton Park Development Center. The different categories of the participants drawn into the sample enabled the researcher to holistically capture how the development process unfolded. The findings of the research indicated that the development model used at Tembisa / Kempton Park Development Center is largely participatory. The model allowed community members to have more say and control in the initiation, design, implementation, monitoring and evaluation of the projects. However this model has challenges that are institutional, social and structural of nature and barriers which hinder effective and meaningful community participation. Government intervention was recommended to address some of the challenges to community participation on a macro level.
Keywords: Participation; Social development; Development Center; Income generating projects; Funders; Beneficiaries; Non-Governmental Organization; Empowerment; People-centered development